An Open‐Label Phase II Trial of Bevacizumab plus Docetaxel and Gemcitabine in Advanced, Previously Untreated Nonsquamous Non‐Small Cell Lung Cancer. (2nd January 2019) - Patil, Pradnya Dinkar; Shapiro, Marc; Hashemi Sadraei, Nooshin; Pennell, Nathan A.
Abstract: Lessons Learned: The combination of bevacizumab with docetaxel‐gemcitabine resulted in unacceptable toxicity, particularly a high rate of pulmonary toxicity (30%). Despite promising efficacy, excessive toxicity of this regimen does not support its use in patients with advanced nonsquamous non‐small cell lung cancer. Background: Prior to immunotherapy, standard treatment for advanced non‐small cell lung cancer (NSCLC) was platinum doublet chemotherapy. In a previous phase II study, docetaxel‐gemcitabine demonstrated comparable efficacy and tolerability to platinum doublets. In this phase II trial, we evaluated the efficacy and tolerability of adding bevacizumab to docetaxel‐ gemcitabine in patients with advanced nonsquamous NSCLC. Methods: Patients with untreated advanced nonsquamous NSCLC were treated with up to six cycles of docetaxel‐gemcitabine‐bevacizumab, followed by bevacizumab until progression. The primary endpoint for this study was 1‐year progression‐free survival (PFS); secondary endpoints were safety, overall response rate (ORR) and overall survival (OS). The planned sample size was 46 patients. Results: A total of 13 patients were enrolled and received a median of six cycles of chemotherapy and four cycles of bevacizumab. The treatment was poorly tolerated, with five patients requiring dose reduction and four discontinuing treatment for toxicity. Grade 3–5 nonhematologic toxicity was seen in 10 patients, and 4 (30%) were hospitalized with pulmonary toxicity possibly related to study drugs. At this point, enrollment was halted for safety concerns. The 12‐month PFS was 8%. In 11 evaluable patients, ORR was 72%, median PFS 6 months, and median OS was 11 months. Conclusion: Docetaxel, gemcitabine, and bevacizumab at this dose and schedule resulted in excessive toxicity. Despite promising efficacy, in light of efficacious and safe alternative therapies, this regimen should not be used to treat advanced NSCLC.